A facile process combined with inkjet printing, surface modification and electroless deposition to fabricate adhesion-enhanced copper patterns on flexible polymer substrates for functional flexible electronics. (10th November 2016) - Wang, Yan; Wang, Yu; Chen, Jin-ju; Guo, Hong; Liang, Kun; Marcus, Kyle; Peng, Qi-ling; Zhang, Jing; Feng, Zhe-sheng
Abstract: A reliable and low-cost method to synthesize high-adhesion and low-resistivity copper patterns on flexible polymer substrates via inkjet printing combined with surface modification and electroless deposition (ELD) is demonstrated in this paper. Through the surface modification of self-assembled monolayers (SAMs), polyethylene terephthalate (PET) substrates were capable of adsorbing the inkjet-printed silver ions ink, which could catalyze the ELD of conductive copper patterns. The fact that SAMs could obviously enhance the adhesion between flexible polymer substrates and copper layers was confirmed by characterizing the physical and chemical properties of SAMs and copper layers using XPS, FT-IR, OM, SEM and EDS. Moreover, after 30 min ELD, the resulting copper layer presented good adhesive strength and a low resistivity of 2.06 × 10 −6  Ω cm, while maintaining reliability even after over 1000 times of bending and mechanical stress. This means that the dependable technology has great potential applications in functional electronics, including flexible circuits and devices.